2013
DOI: 10.1080/07373937.2013.796968
|View full text |Cite
|
Sign up to set email alerts
|

Spray Drying of Monoclonal Antibodies: Investigating Powder-Based Biologic Drug Substance Bulk Storage

Abstract: Biologic drug substances (DSs) are stored and transported as frozen bulk in various containers, each having disadvantages. We evaluated a powder-based bulk storage approach based on spray drying and demonstrate for the first time that monoclonal antibodies (mAbs) can be spray dried with >90% powder collection yield using a laboratory-scale spray dryer, which outperformed three benchtop units in yield and water content reduction. Cyclone design was critical to collection yield, which remained sensitive to sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…In this study, the theoretical BSA loading was 8.81% w/v while the actual BSA loading was 8.35% w/v, hence the loading efficiency was calculated as 94.8%, which is higher than the typical recovery rate in spray drying (46, 47). As shown in Table I, among the recovered beads, there were very few agglomerated beads (2.95%), but lots of fines (10.83%), especially between 300 to 355 microns, which suggested the potential attrition of beads during the process.…”
Section: Resultsmentioning
confidence: 77%
“…In this study, the theoretical BSA loading was 8.81% w/v while the actual BSA loading was 8.35% w/v, hence the loading efficiency was calculated as 94.8%, which is higher than the typical recovery rate in spray drying (46, 47). As shown in Table I, among the recovered beads, there were very few agglomerated beads (2.95%), but lots of fines (10.83%), especially between 300 to 355 microns, which suggested the potential attrition of beads during the process.…”
Section: Resultsmentioning
confidence: 77%
“…The fact that material recovery is <100% is also an issue when considering its implementation for high‐cost therapeutics. Still, proper process design can overcome many of these limitations, highlighting the great potential of spray drying as an alternative to lyophilization that may enable continuous manufacturing …”
Section: Spray Dryingmentioning
confidence: 99%
“…Still, proper process design can overcome many of these limitations, highlighting the great potential of spray drying as an alternative to lyophilization that may enable continuous manufacturing. 146…”
Section: Spray Drying Summarymentioning
confidence: 99%
“…Bowen et al [7] evaluated the feasibility of spray drying several mAbs in a trehalose-based formulation using similar dryers. In the initial study, >95% recovery was reported for mAbs processed using MS-35.…”
Section: Spray Dryingmentioning
confidence: 99%